2005
DOI: 10.1038/sj.emboj.7600526
|View full text |Cite
|
Sign up to set email alerts
|

Identification of neuromedin S and its possible role in the mammalian circadian oscillator system

Abstract: The discovery of neuropeptides has resulted in an increased understanding of novel regulatory mechanisms of certain physiological phenomena. Here we identify a novel neuropeptide of 36 amino-acid residues in rat brain as an endogenous ligand for the orphan G protein-coupled receptor FM-4/TGR-1, which was identified to date as the neuromedin U (NMU) receptor, and designate this peptide 'neuromedin S (NMS)' because it is specifically expressed in the suprachiasmatic nuclei (SCN) of the hypothalamus. NMS shares a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
195
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(205 citation statements)
references
References 54 publications
6
195
0
Order By: Relevance
“…Interestingly, a novel 33-residue peptide derived from the NMU proprotein has recently been identified and shows potent prolactin-releasing activity when administered i.c.v. (Williams et al 2001, Mori et al 2005. In the present study, the interaction of nutritional status and leptin with NMU gene expression in the pars tuberalis is clearly evidenced.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Interestingly, a novel 33-residue peptide derived from the NMU proprotein has recently been identified and shows potent prolactin-releasing activity when administered i.c.v. (Williams et al 2001, Mori et al 2005. In the present study, the interaction of nutritional status and leptin with NMU gene expression in the pars tuberalis is clearly evidenced.…”
Section: Discussionsupporting
confidence: 55%
“…The NMU probe used in the present study has a portion of overlap with the known gene sequence of neuromedin S (NMS) and the possibility exists that some of the signal located in the present study corresponds to NMS gene expression. However, this is unlikely as NMS is almost exclusively localised to the SCN and its occurrence in the pars tuberalis has not been reported despite sections containing the closely neighbouring arcuate nuclei being observed (Mori et al 2005). …”
Section: Localisation Of Nmu and Ob-rb Gene Expressionmentioning
confidence: 98%
“…Mammalian NMU and NMS share the C-terminal heptapeptide-amide 1a (H-Phe 0 -Leu 1 -Phe 2 -Arg 3 -Pro 4 -Arg 5 -Asn 6 -NH 2 , Figure 1A), which activates both receptors. 1,2 In 1995, Hashimoto et al reported that N-terminal succinylated 1a, which was synthesized as an aminopeptidase-resistant derivative, showed potent contractile activity toward chicken crop smooth muscle expressing avian NMU receptors. 10 Recently, we performed a structure−activity relationship (SAR) study of heptapeptide 1a to develop receptor-selective agonists using cultured cells expressing human NMU receptors.…”
mentioning
confidence: 99%
“…In contrast, they strongly suggest the involvement of NMU in the physiological regulation of the biological activity of immature rat adrenocortical cells. It has been suggested that NMU exerts its biological effects mainly via autocrine-paracrine mechanisms (53). However, the expression of NMU gene was not detected in the rat adrenals (33).…”
Section: Discussionmentioning
confidence: 97%